ANALISIS PEMAHAMAN MAHASISWA TENTANG HAK DAN KEWAJIBAN WARGA NEGARA DI ERA DIGITAL - Hasan, Riza (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to explore the understanding of West Aceh State Community Academy students about digital citizenship in the context of Aceh's local values. The descriptive qualitative method was used with case studies at the research site. Data were collected through in-depth interviews, FGDs, participatory observations, and document analysis. The results of the study show that Acehnese religious values and customs have a significant influence in shaping students' perceptions of digital citizenship. The findings also highlight gaps in the understanding of digital citizenship and difficulties in evaluating the correctness of online information. The shortcoming of this study is the lack of concrete recommendations for action. Therefore, further research is recommended to further explore the interaction between traditional values and digital modernity, as well as develop educational strategies that are responsive to local contexts but remain globally relevant.